Um estudo sobre o conceito de história e tempo presente em Marx através da crítica da economia política de 1859 - Menezes, Jean Paulo Pereira de [UNESP] (2015)
The submitted thesis deals with a study about the concept of history and present time. Our starting point was the Karl Marx's publication of 1859 entitled Zur Kritik der Politschen Ökonomie (For the Critic of the Political Economy). The following presented object does not pretend to occupy itself with a study situated in the present time (although clearly departs from it) neither of understanding Marx as a historian, even less, a historian of present time. This is a theoretical study, classified as bibliographical-documental, located in the whereabouts of XIX century, and this present the font's type we utilize. However, it becomes indispensable to take in consideration the concept of history and present time in its historical totality, occupying us of a part of Marx's trajectory and the construction of these central concepts. In XX century, a part of the French historiography dedicated itself to the study of present time, synthesizing a theoretical-methodological frame in the sixties, although, distant from Marx, because of its particularities. Marx, before all the important formulations institutionalized in the Centre National de la Recherche Scientifique, through the Institut d'histoire du temps present, already worked with a concept of history and present time outside the university, which enabled him a kind of intellectual production improbable if done in the academy. This is a central question in the construction of the concept of history and present time in the author and so significant it had historic-social repercussion even in the academy. We study here two concepts intrinsically connected and even though having as starting point a Marx's work we couldn't restraint ourselves to it for so we could systematize his own understanding. The study about Marx thematically is really vast, however, we postulate that there is still much to explore about the theoretical and methodological perspective developed by Marx in his...